2019
DOI: 10.1055/a-0810-3516
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Delayed-Onset Muscle Soreness (DOMS) – Part II: Treatment and Prevention

Abstract: Delayed-onset muscle soreness (DOMS) describes an entity of ultrastructural muscle damage. The manifestation of DOMS is caused by eccentric muscle contractions or unaccustomed forms of exercise. Clinical signs include impaired muscular force capacities, painful restriction of movement, stiffness, swelling, and altered biomechanics in adjacent joints. Although DOMS is categorised as a mild type of muscle damage, it is one of the most common reasons for compromised sportive performance. In the last decade, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 84 publications
1
67
0
Order By: Relevance
“…Based on pathophysiological foundations, studies on compression focus on different time-dependent application modes, including "during exercise" (i.e., biomechanical support) and "post-exercise" treatment aiming to limit the in ammatory processes mentioned above and thereby preventing the development and clinical signs of DOMS (2). A meta-analysis found that several studies described recovery-enhancing effects for wearing compression garments both during exercise and afterwards, whereas other studies were not able to con rm these ndings (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on pathophysiological foundations, studies on compression focus on different time-dependent application modes, including "during exercise" (i.e., biomechanical support) and "post-exercise" treatment aiming to limit the in ammatory processes mentioned above and thereby preventing the development and clinical signs of DOMS (2). A meta-analysis found that several studies described recovery-enhancing effects for wearing compression garments both during exercise and afterwards, whereas other studies were not able to con rm these ndings (30).…”
Section: Discussionmentioning
confidence: 99%
“…High-performance sports and the importance of achieving peak physical capacity and performance have led athletes and coaches to continually seek treatments or techniques that may improve regeneration and recovery (1)(2)(3). The rate and quality of recovery has been considered to be essential for both elite and recreational athletes during repetitive training or competition (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to perform eccentric resistance training to achieve positive adaptations is inherent to the development of DOMS, but a solid and consistent treatment for DOMS has not been established to date. Although there are multiple practices for DOMS alleviation, only a few of them have scientific support ( Connolly et al, 2003 ; Heiss et al, 2019 ). The most well-known therapeutic programs for the management of DOMS include cryotherapy, stretching, massage, use of compression during or after exercise, ultrasound muscular treatment, or oral non-steroidal anti-inflammatory drugs (NSAIDs) ( Matsumura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although DOMS plays an important role in muscle remodeling and favorable adaptations [ 3 ], its extended duration may occasionally jeopardize exercise routine and cause more harm than good. This being the case, many approaches have been developed to optimize DOMS recovery, yet the treatment and prevention options remain somewhat limited [ 4 ]. Hydrogen-rich water (HRW) has been put forward lately as a worthwhile therapeutics in musculoskeletal medicine.…”
Section: Introductionmentioning
confidence: 99%